INTERNASIONALISASI MAJALAH INDONESIA - Hendrarta Kusbandarrumsamsi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2000)
Internationalization of lndonesian journals is an effort to promote the Indonesian journals over the world. The responsibility of PDII-LIPI as a National Center ofiSDS is to report regularly the Indonesian journals to International Center of ISDS in French. This activities is a form of internationalization oflndonesianjournals. Three lists of international journals has been studied. There are 7,165 titles of indonesian journals which have ISSN during 1978-1997. But, less than 100 titles were covered in the lists of international journals, while the internationalization of LIPI's journals were only 15 titles.